Antoxidant enzymes in the liver and gills of Tinca tinca from various water bodies. (June 2014) - Drozd, R.; Panicz, R.; Jankowiak, D.; Hofsoe, P.; Drozd, A.; Sadowski, J.
Summary: The activity of antioxidant enzymes [superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT) and glutathione‐S‐transferase (GST)] in the liver and gills of tench ( Tinca tinca L.) from distinct habitats were studied. Fish were collected in the same season from three different water bodies: a cage culture supplied with cooling water from a power plant; traditional aquaculture in fishponds; and from the Odra River estuary. In all water bodies, the activity of antioxidant enzymes was significantly higher in the liver than in the gills. The highest activities of GST in the liver and GPx in the gills were detected in tench from the Odra River estuary, which may suggest abiotic stress connected with water quality in the estuary.